GAMBARAN PERILAKU MEROKOK, POLA MAKAN, PERILAKU AKTIVITAS FISIK DAN POLA TIDUR MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TANJUNGPURA - ., Suharto (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Everyone have risk for unhealthy behavior, includingmedical students. The study in medical students of Diponegoro University,found that 4.9% are smokers, 51.1% have unhealthy eating patterns,61.4% have worse physical activity, and 47.8% poor sleep patterns. Everybehavior that is incompatible with the principles of healthy living will lead todiseases and for medical students it will have an impact on the decline ofpublic trust in health care when they become health workers. Objective:this study aims to know the description of health behavior consisting ofsmoking behavior, diet, physical activity, and sleep patterns in medicalstudent of Tanjungpura University. Method: This study is a descriptivecross sectional. It was do at Medical Faculty of Tanjungpura University inDecember 2011-January 2012. Subjects were medical student class of2008-2011 that meets the criteria. The total samples are 157 respondents.Processing and data analysis is descriptively and presented in table ofdistribution, frequency and textually. Results: All respondents did notsmoke. About 88.5% (n=139) have good diet, 37.6% (n=59) good physicalactivity, and 91.7% (n=144) with good sleep patterns. By class years,class of 2008 is better diet than another (93.9%), 2009 is better forphysical activity than another (42.2%), and class of 2011 is better in sleeppattern (97,4%). Conclusion: In general, smoking behavior, diet, andsleep patterns respondent in accordance with the principles of healthyliving. For physical activity behavior, more of them are worse. So it issuggested that medical students of Tanjungpura University could dohealthy behaviors consistently and for medical institutions can providedepth material about healthy behavior.Key words: smoking, diet, physical activity behavior, sleeps patterns